Synthesis of ZSM-5 monoliths with hierarchical porosity through a steam-assisted crystallization method using sponges as scaffolds - Hu, T.; Liu, Jian; Cao, C.; Song, W. (2017)
© 2017, Dalian Institute of Chemical Physics, Chinese Academy of Sciences. Published by Elsevier B.V. All rights reserved. Self-supporting ZSM-5 crystals with hierarchical porosity were prepared through a steam-assisted crystallization method using sponges as rigid scaffolds. The synthesized materials were characterized by X-ray diffraction, nitrogen sorption, scanning electron microscopy, transmission electron microscopy, solid-state nuclear magnetic resonance spectroscopy and ammonia temperature-programmed desorption. The ZSM-5 monoliths exhibited high crystallinities, hierarchical porous structures and strong acidities. They showed superior catalytic performance in the liquid-phase esterification reaction between benzyl alcohol and hexanoic acid.